Efek Residu Kompos dengan Komposisi Biochar yang Berbeda dan Penggunaan Tanah Bekas Penanaman Beberapa Jenis Kacang Lokal terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis hypogeae L.) di Lahan Kering Entisol pada Tahun Kedua - Auxilia Nahak (Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the effect of compost residue with biochar composition and the use of soil used for planting several types of lokal beans and their interaction on the growth and yield of peanuts (Arachis hypogeae L.) in Entisol dry land in the second year. This research in February – June 2020 at the Experimental Field of the Faculty of Agriculture, University of Timor. This study used a 4x3 Randomized Block Design (RAK) which was repeated three times. The first factor is compost residue (K) consisting of 4 (four) levels, namely: No Compost (K0), Pure Compost, 25% Biochar, 50% Biochar. The second factor is the entisol soil that has been planted with lokal beans (T) which consists of 3 (three) levels, namely: Land without planting lokal beans, string beans, rice beans, so that there are 12 treatment combinations + 6 control land units so there are 36 units. experimental unit. The results showed that there was no interaction between the treatment of residues of biochar composition and the type of lokal bean residue on the growth and yield of peanuts. Treatment of residues of 25% biochar composition was able to increase the growth and yield of peanut plants which showed high parameters. the highest plant weight was 100 seeds, seed weight per plot, plant fresh weight, plant dry weight, and harvest index. Treatment of lokal bean residue type, namely rice beans, was able to increase root length, number of root nodules, dry weight of stover and garden seed weight.